Application of Peer Tutor Method to Improve Basic Sickle Kick Technique Skills in Pencak Silat - Juyinah Juyinah (Journal of Business, Social and Technology, 2022)
This research, which focuses on teachers' efforts to improve activities and student learning outcomes in learning basic sickle kick techniques using the peer tutoring method, is carried out in order to improve teacher and student performance in an innovative and collaborative manner. This study aims to improve the quality of the process and student learning outcomes that were previously known to not meet learning expectations. This research was conducted on third grade students of SD Negeri 1 Bade, Klego District, Boyolali Regency. The research design used is an action research design whose flow is to make action plans, carry out actions in learning, observe actions, and reflect on actions. The results of these reflections are used to make decisions. The research data are in the form of field notes, observation notes, planning documentation. The collection instruments are observation guidelines, field notes, and documentation. Data analysis using a qualitative flowing approach includes stages of data reduction, data exposure, verification, and data inference. To test the validity of the data, triangulation is carried out with collaborators and students. completing this research, the authors can conclude as follows. The peer tutoring method can increase the activity and learning outcomes of Class III students of SD Negeri 1 Bade, Klego District in learning basic sickle kick techniques. The average value of the student learning process in the first cycle is 78.5. The acquisition of the average value of student learning outcomes in cycle II, which is 86.3.